ANALISYS OF HEAVY METAL CONCENTRATIONS IN SEAWATER AND SEDIMENT OF THE WEST COAST OF KARIMUN BESAR ISLAND RIAU ARCHIPELAGO - Martinus Jerianto; Bintal Amin; Yusni Ikhwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted in January 2015 to determine the heavy metal concentration of lead (Pb) and copper (Cu) in seawater and sediment in the west coast of Karimun Besar Island of Riau Archipelago. Samples of sea water and sediment were analyzed for their metal concentrations in Marine Chemistry Laboratory Department of Marine Sciences University of Riau Pekanbaru by using AAS Perkin Elmer 3110. Metal concentrations in the sea water were highest in Station I (Pb 0.270 mg/L and Cu 0.140 mg/L), whilst concentrations in the sediment were found to be highest in stations III (Pb 8.055 μg/g, Cu 5.359 μg/g). Concentrations of Pb and Cu in the sediment in the study area was still below the Dutch quality standard for metals in sediments and the default value of the ERL and ERM. Based on I-geo calculations it was considered that the study area still has low impact on aquatic ecology.Key Words: heavy metal, seawater, sediment, Karimun, Lead, Copper